OP0257 Decrease of autophagy in peripheral blood mononuclear cells from systemic lupus erythematosus patients treated with belimumab. (12th June 2018) - Colasanti, T.; Spinelli, F.R.; Barbati, C.; Massaro, L.; Ceccarelli, F.; Vomero, M.; Morello, F.; Orefice, V.; Conti, F.; Valesini, G.; Alessandri, C.
Abstract : Background: Autophagy is a conserved catabolic process that degrades cytoplasmic constituents and organelles in the lysosome, promoting the recycling of cellular nutrients, and is also a key mechanism for protein homeostasis and quality control 1 . T lymphocytes from patients with systemic lupus erythematosus (SLE) are resistant to induction of autophagy 2 . Belimumab (BLM), a human monoclonal antibody that inhibits B lymphocyte stimulator (BLyS), is the first biological drug to be approved for the treatment of SLE. BLM seems to play a role in modulating the signalling cascade involved in the regulation of autophagy, blocking the binding of soluble BLyS to its receptors (B cell activating factor receptor, BAFF-R; B cell maturation antigen, BCMA; transmembrane activator and calcium modulator and cyclophilin ligand interactor, TACI), mainly expressed on B cells and plasmacells 3 . Objectives: The aim of this study was to evaluate the autophagy process by means the expression of LC3-II and p62 markers in lysates of peripheral blood mononuclear cells (PBMCs) from SLE patients at baseline (t0) and after 2 weeks (t2weeks), 1 month (t1month), and 3 months (t3months) of treatment with BLM. We also investigated the presence of BLyS receptors on T cell subsets. Methods: We enrolled 15 consecutive patients who started treatment with BLM (M/F, 0/15; mean age, 44.3 years, range 30–54 years; mean disease duration, 242.6 months, range 48–432 months). All patients fulfilled the American College of Rheumatology revised classification criteria 4 . PBMCs from SLE patients were lysed in lysis buffer and analysed to evaluate autophagy, monitoring LC3-II and p62 levels by Western blot. Flow cytometry was performed for surface phenotyping of freshly isolated PBMCs, using conjugated monoclonal antibodies against human CD4 and CD8; anti-human BAFF-R, BCMA, and TACI polyclonal antibodies were used to detect BLyS receptors on T cells subsets. Results: LC3-II expression levels in PBMCs from SLE patients decreased after 3 months of BLM therapy and, in the same lapse, p62 levels increased (figure 1; p<0.05 for all the experimental conditions). BAFF-R and BCMA were expressed on CD4 + (Mean Fluorescence Intensity -fold increase-, MFI=1.6 and 1.2, respectively; p<0.05) and CD8 + (MFI=1.6 and 2.5; p<0.05) T cells, while TACI was expressed only on CD8 + T cells (MFI=1.2; p<0.05). Conclusions: In the present study we demonstrated, for the first time, the expression of BAFF-R, TACI and BCMA in CD4 + and CD8 + T cells from SLE patients, and that BLM treatment was able to decrease the levels of autophagy in PBMCs. We can speculate that BLM could mediate this effect by blocking the binding of BLyS with its receptors. References: [1] Kaur, Debnath. Autophagy at the crossroads of catabolism and anabolism. Nat Rev Mol Cell Biol2015;16:461–72. [2] Alessandri, et al. T lymphocytes from patients with systemic lupus erythematosus are resistant to induction of autophagy. FASEB J2012;26:4722–32. [3] Rockel, Kapoor. Autophagy: controlling cell fate in rheumatic diseases. Nat Rev Rheumatol2016;12:517–31. [4] Hochberg. Updating the American College of Rheumatology revised criteria for the classification of systemic lupus erythematosus. Arthritis Rheum1997;40:1725. Disclosure of Interest: None declared